The Role of Synbiotics in Modulating the Gut–Brain Axis in Attentiondeficit/Hyperactivity Disorder: A Systematic Review - Elfrida Noor Auliya; Margarita M. Maramis (Jurnal Sehat Indonesia (JUSINDO), 2026)
ADHD is a neurodevelopmental disorder involving gut microbiota dysbiosis and gut–brain pathways, suggesting synbiotics as a potential adjuvant therapy. Literature searches were conducted on electronic primary databases "PubMed", "EuropePMC", and "ScienceDirect" with a range published between 2020–2025. Studies were selected based on inclusion criteria and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The methodological quality of the included studies was evaluated using the Joanna Briggs Institute (JBI) Critical Appraisal Tools for randomized clinical trials. Of the 146 articles identified, five randomized clinical trial studies met the inclusion criteria. The available evidence suggests that synbiotic interventions have varied clinical effects in ADHD patients. More obvious benefits are mainly seen in the symptomatic aspects of inattention, with secondary impacts on impulse control and adaptive function of daily behavior, as well as inflammatory biomarkers and gut microbiota. No serious side effects were reported in any of the included studies. This systematic review suggests that synbiotics have the potential to modulate the two-way gut-brain communication pathway and provide domain-specific clinical benefits in subgroups of ADHD patients with specific clinical or biological characteristics. These findings support the role of synbiotics as adjuvant therapy, but are not enough to recommend it as a single therapy for the entire ADHD patient population in general.